Effectiveness of Dance Movement Therapy in the Treatment of Adults With Depression: A Systematic Review With Meta-Analyses - Karkou, Vicky; Aithal, Supritha; Zubala, Ania; Meekums, Bonnie (Frontiers in Psychology, 2019)
Background: Depression is the largest cause of mental ill health worldwide. Although interventions such as Dance Movement Therapy (DMT) may offer interesting and acceptable treatment options, current clinical guidelines do not include these interventions in their recommendations mainly because of what is perceived as insufficient research evidence. The 2015 Cochrane review on DMT for depression includes only three RCTs leading to inconclusive results. It is therefore, necessary to also look beyond such designs in order to identify and assess the range of current evidence. Methods: We therefore, conducted a systematic review of studies that aimed to explore the effectiveness in the use of DMT with people with depression. This led to a qualitative narrative synthesis followed by a subgroup analysis and a sensitivity analysis. In all meta-analyses a random effects model was used with Standardised Mean Differences (SMD) to accommodate for the heterogeneity of studies and outcome measures. Results: From the 817 studies reviewed, eight studies met our inclusion criteria. 351 people with depression (mild to severe) participated, 192 of whom attended DMT groups while receiving treatment as usual (TAU) and 159 received TAU only. Qualitative findings suggest there was a decrease in depression scores in favour of DMT groups in all studies. Subgroup analysis performed on depression scores before and three months after the completion of DMT groups suggested changes in favour of the DMT groups. When sensitivity analysis was performed, RCTs at high risk of bias were excluded, leaving only studies with adult clients up to the age of 65. In these studies, the highest effect size was found favouring DMT plus TAU for adults with depression, when compared to TAU only. Conclusions: Based on studies with moderate to high quality, we concluded that DMT is an effective intervention in the treatment of depression with adults. Furthermore, by drawing on a wide range of designs with diverse quality, we were able to compile a comprehensive picture of relevant trends. Despite the fact that there remains a paucity of high-quality studies, the results have relevance to both policy-making and clinical practice, and become a platform for further research.